The business of giving - LOW, Eunice (Institutional Knowledge at Singapore Management University, 2017)
Paul Dunn is shaping a new generation of socially conscious businesses by providing a sustainable platform that connects company with cause. When it comes to giving, Paul Dunn means business—literally. As the chairman of Buy1Give1 (B1G1), the 72-year-old oversees a social enterprise devoted to making business philanthropy a more effortless process. A firm believer that it is in giving that one receives (joy, that is), he tells EUNICE RACHEL LOW and CHRISTIAN PETROSKE how joy, rather than duty or guilt, sustains giving corporations.